Novel benzo[α]phenoxazinium chlorides functionalized with sulfonamide groups as NIR fluorescent probes for vacuole, endoplasmic reticulum, and plasma membrane staining - Ferreira, J. C. C. (2023)
The demand for new fluorophores for different biological target imaging is increasing. Benzo[a]phenoxazine derivatives are fluorochromophores that show promising optical properties for bioimaging, namely fluorescent emission at the NIR of the visible region, where biological samples have minimal fluorescence emission. In this study, six new benzo[a]phenoxazinium chlorides possessing sulfonamide groups at 5-amino-positions were synthesized and their optical and biological properties were tested. Compared with previous probes evaluated using fluorescence microscopy, using different S. cerevisiae strains, these probes, with sulfonamide groups, stained the vacuole membrane and/or the perinuclear membrane of the endoplasmic reticulum with great specificity, with some fluorochromophores capable of even staining the plasma membrane. Thus, the addition of a sulfonamide group to the benzo[a]phenoxazinium core increases their specificity and attributes for the fluorescent labeling of cell applications and fractions, highlighting them as quite valid alternatives to commercially available dyes.